فاعلية العناصر المكونة للإيقاع البصري وإشتغالاتها في العرض المسرحي: عرض مسرحية مكاشفات انموذجا - إبراهيم، أنعام معن (الجمعية العلمية للدراسات التربوية المستدامة, 2024)
إن فضاءات العرض المسرحي مرتبطة بعدة اشتراطات تمثلها مجموعة من الاتجاهات والمدارس والأساليب والطرائق التي تنتهج منهجا يتماشى مع تلك الطروحات الفكرية والفنية والجمالية والتقنية لتلك العروض المسرحية، فضلا عن أن المشترك الأهم في تلك الطروحات هو ضبط الإيقاع بشكل عام، فضلا عن فاعلية العناصر المكونة للإيقاع البصري في الفضاء الدرامي، كما أن عناصر الإيقاع البصري تتسم بسمات مشابهة لسمات الاتجاه أو الأسلوب المتبع في العرض سواء كان واقعيا أم ملحميا أم سرياليا، فلكل أسلوب إيقاعه الخاص به، فتتجلى تلك العناصر عبر المنظومة البصرية بإيقاعاتها المغايرة، وتحاول (الباحثة) في بحثها هذا أن تتطرق إلى الإجراءات المتشكلة لتفعيل العناصر المكونة للإيقاع البصري ومعرفة آلية اشتغالها في منظومة العرض المسرحي، لان الإيقاع البصري من اهم المرتكزات التي يحقق بها المخرج رؤيته الفنية والجمالية والتقنية والفكرية، ولهذا جاء عنوان البحث تحت مسمى (فاعلية العناصر المكونة للإيقاع البصري واشتغالاتها في العرض المسرحي). Theatrical performance spaces are linked to several requirements represented by a group of directions, schools, methods and modalities that adopt an approach that is in line with those intellectual, artistic, aesthetic and technical proposals for these theatrical performances, in addition to that the most important common in these proposals is to control the rhythm in general, as well as the effectiveness of the components of the visual rhythm In the dramatic space, just as the elements of visual rhythm are characterized by features similar to the features of the direction or the style used in the show, whether it is realistic, epic or surreal, each style has its own rhythm, so these elements are manifested through the visual system with their different rhythms, and the (researcher) tries in her research this To address the procedures formed to activate the constituent elements of the visual rhythm and to know the mechanism of their operation in the theatrical performance system, because the visual rhythm is one of the most important pillars by which the director achieves his artistic, aesthetic, technical and intellectual vision.
Keywords: العروض المسرحية -- الفضاء المسرحي -- الإيقاع البصري